Insights into the use of metal complexes of thiourea derivatives as highly efficient adsorbents for ciprofloxacin from contaminated water. Issue 2 (4th May 2019) - Akpomie, Kovo G.; Fayomi, Omotola M.; Ezeofor, Chidinma C.; Sha'Ato, Rufus; Van Zyl, Werner E.
Abstract : Despite the wide use of synthesised metal complexes of thiourea and their derivatives in medicine and corrosion inhibition, a paucity of research exists on their application as adsorbents for pollutants. This study was aimed at investigating the adsorption potential of the copper (II) and zinc (II) complexes of 4-nitro-substituted thiourea derivatives of aminophenol for ciprofloxacin (CPF). The metal complexes were synthesised and characterised. Fourier transform infrared spectroscopy, scanning electron microscopy and a BET surface area analyzer were utilised to determine the surface structure and properties of the synthesised adsorbents. Isotherms were conducted by the application of Langmuir, Freundlich and Scatchard models and revealed a heterogeneous multilayer adsorption process. Kinetic evaluation showed best fit with the pseudo second order model ( R 2  > 0.991) compared to the pseudo first order and Bangham equations. Thermodynamics showed an endothermic spontaneous abstraction process. The metal complexes showed over 80% desorption of CPF using 0.2 M NaOH and were stable over three cycles of regeneration and reuse. This research revealed the potential of the metal complexes of thiourea as adsorbents for CPF supported by the high adsorption capacity compared to other reported adsorbents.